silver n/ silver (fox (1987)
silver n He paid out $150 for a silver fox, male. PRINTED ITEM DNE Sup [Add to DNE silver n 2, to 1956 cite] G.M.Story NOV. 3 1987 WK Used I and Sup Used I and Sup 2 Used Sup ~ fir/fox/hair (fox)/jar/thaw/ patch fox, GLITTER, PATCH FOX.